2002
DOI: 10.1007/s00347-002-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Nekrotisierende ulzerierende Keratopathie nach Lokalanästhetikamissbrauch

Abstract: Silicone oil can penetrate the corneal stroma in cases of defects in Descemets' membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Among the effective compounds tested, pentamidine isethionate inhibited synthesis of DNA, RNA, phospholipids, and proteins, with amoebicidal and cysticidal properties seen at ϳ100 to 200 g per ml with variable results (11,19,73), while propamidine isethionate (DNA synthesis inhibitor) is used clinically against keratitis at a concentration of up to 1 mg per ml (13,16,17,23,27,32,33,35,36,38,42,46,53,70,(74)(75)(76)(77)(78)(79). Other drugs tested included diminazene aceturate, which binds to the groove between the complementary strands of DNA at regular intervals and thus distorts the helical structure.…”
Section: Nucleic Acid-acting Drugsmentioning
confidence: 99%
“…Among the effective compounds tested, pentamidine isethionate inhibited synthesis of DNA, RNA, phospholipids, and proteins, with amoebicidal and cysticidal properties seen at ϳ100 to 200 g per ml with variable results (11,19,73), while propamidine isethionate (DNA synthesis inhibitor) is used clinically against keratitis at a concentration of up to 1 mg per ml (13,16,17,23,27,32,33,35,36,38,42,46,53,70,(74)(75)(76)(77)(78)(79). Other drugs tested included diminazene aceturate, which binds to the groove between the complementary strands of DNA at regular intervals and thus distorts the helical structure.…”
Section: Nucleic Acid-acting Drugsmentioning
confidence: 99%
“…[10] To our knowledge, this is the first report identifying intracorneal migration of intraocular silicone oil. The postulated route of entry of silicone oil into the corneal intrastromal space is via the breaks in the Descemet's layer.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this patient was a medical doctor himself. [22] Yagci et al . (2011) reported that out of 19 men (26 eyes) admitted to hospital, ten patients (52.6%) reported that they were using topical anesthetics and the remaining nine were discovered to have been using topical anesthetic drops during hospitalization.…”
Section: Discussionmentioning
confidence: 99%